Evaluation of thrombin generation in dogs administered clopidogrel - Rank, Kaitlyn; Lynch, Alex M.; Ruterbories, Laura K.; Li, Ronald H. L.; Ueda, Yu (Frontiers in Veterinary Science, 2023)
The antiplatelet effect of clopidogrel can vary between patients. A modified thromboelastography (TEG) protocol (TEG-Platelet Mapping assay® [TEG-PM]) can be used for clopidogrel monitoring but is not widely available. Thrombin generation (TG) assays could offer a novel alternative. The main objective of this pilot study was to assess TG assay variables (lag time, peak, endogenous thrombin potential [ETP]) in dogs before and after 7 days of clopidogrel administration and compare with TEG-PM variables (maximum amplitude [MA]-ADP and percentage (%) inhibition). Six healthy mix-breed dogs were enrolled in this pilot study. Blood samples for platelet count, TG assays, and TEG-PM were obtained at two time points, corresponding to baseline, and after 7 days of clopidogrel administration (mean 2.3 +/- 0.3 mg/kg PO q24 hours). Data were then compared with a Student’s t-test. There was no significant change in TG assay variables performed on platelet poor plasma after 7 days of clopidogrel administration: lag time (Day 1: 1.8 +/- 0.2 min, Day 7: 1.8 +/- 0.2 min, P=0.42); Peak (Day 1: 76 +/- 7 nM, Day 7: 72 +/- 10 nM, P=0.49); and ETP (Day 1: 399 +/- 27 nM*min, Day 7: 392 +/- 32 nM*min; P=0.49). There were significant changes in TEG MA-ADP (Day 1: 19 +/- 8 mm, Day 7: 9 +/- 6 mm, P=0.04) and % inhibition (Day 1: 58 +/- 27, Day 7: 99 +/- 0.3, P=0.02). however over the course of the study. Clopidogrel administration did not lead to changes in TG assay variables performed on platelet poor plasma samples, despite concomitant changes in TEG-PM variables consistent with platelet inhibition. Based on this pilot study, thrombin generation performed on platelet poor plasma may not be a useful antiplatelet monitoring tool in dogs.